2017
DOI: 10.13066/kspm.2017.12.1.83
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stretching and Elastic Band Exercises Knee Space Distance and Plantar Pressure Distribution during Walking in Young Individuals with Genu Varum

Abstract: | Abstract |1 )PURPOSE: The purpose of this study was to investigate the effects of stretching and elastic band exercise on the knee space distance and plantar pressure distribution in people with genu varum. METHODS:The subjects of this study were students of a college who had genu varum of 14 subjects. The subjects were randomly divided into two groups as a stretching group (n=7, 4 males and 3 females, age: 20.14±2.54 years, height:167.1±9.78 cm, weight: 58.6±10.13 kg) and a Thera-band group (n=7, 5 males an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Ghasemi et al (2017) also reported that the TheraBand strengthening program provided a significant effect on girls' genu varum deformity and has improved the alignment of their hip, knee, and ankles due to the weakening of weakened muscles [5]. Park et al (2017) revealed that TheraBand resistance training improved knee deformity and reduced the distance between the knees in this group [15]. Haddadnejad et al (2011) examined the relationship between genu valgum deformity and lower limb strength in adolescent males [30].…”
Section: Discussionmentioning
confidence: 99%
“…Ghasemi et al (2017) also reported that the TheraBand strengthening program provided a significant effect on girls' genu varum deformity and has improved the alignment of their hip, knee, and ankles due to the weakening of weakened muscles [5]. Park et al (2017) revealed that TheraBand resistance training improved knee deformity and reduced the distance between the knees in this group [15]. Haddadnejad et al (2011) examined the relationship between genu valgum deformity and lower limb strength in adolescent males [30].…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to differences in living habits. Most of the population in Eastern countries live sedentary lives, which can cause knee varus [18]. Knee varus legs could cause a foot varus that touches the ground with the outside of the foot.…”
Section: Shoe Abrasion and Gait Patternsmentioning
confidence: 99%